Multi-Semiotic Communications in the Spatio-Temporal Making of Vijayendra Prasad’s Bahubali (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Film has made popular several visual forms of culture across the globe, one of which is Indian anthropology. The objectives behind this study are to inform Indian movies’ audience on what some of their iconic, indexical, symbolic images and visual representations as well as actors’ verbal and non-verbal actions could be interpreted to mean in their various spaces and times of occurrences. Therefore, the researchers are also interested in exploring the socio-cultural complexities that unfold between the spatio-temporal makings of the event series in the film – Bahubali. This paves a way for discerning what motivates many non-Hindi speakers world-wide to watch their films, translated or not translated. The concept of visual grammar, designed by Kress and van Leeuwen in Reading Images: The Grammar of Visual Design (1996; 2006) from the theoretical basis of Halliday’s ‘metafunction’ and O’Toole’s The Language of Displayed Art (1994; 2011) which focus on art works like architecture and sculpture in addition to painting, were employed for data analysis. Hence, this qualitative research of ten (10) randomly select paired-samples from Bahubali, analytically rely on these two foundational books that both contain and capture crucial semiotic resources with non-verbal communication for data analysis. It was found that semiotic spaces of sacrifices, such as that of Shivagami until Shivudu, (the protagonist), was given to his foster father and that of Ballaladeva on the battle field against Kalakenya are spiritual as well as religious. Also, scenarios of promises and fulfillment, bows and respect, songs and festivities, and oath taking and steadfastness are all parts of Indian culture. The paper concludes that the film exudes more of Indian’s cultural, spiritual, religious and conventional attachment through different verbal and non-verbal modes to fulfill semiotic obligations.Keywords: , , , ,
Keywords: Semiotics; multimodal(ity); social semiotics; visual grammar; film making